The paradox of overnutrition in aging and cognition. - Fielding, Roger A; Gunstad, John; Gustafson, Deborah R; Heymsfield, Steven B; Kral, John G; Launer, Lenore J; Penninger, Josef; Phillips, David I W; Scarmeas, Nikolaos (Ann N Y Acad Sci, 2013)
Populations of many countries are becoming increasingly overweight and obese, driven largely by excessive calorie intake and reduced physical activity; greater body mass is accompanied by epidemic levels of comorbid metabolic diseases. At the same time, individuals are living longer. The combination of aging and the increased prevalence of metabolic disease is associated with increases in aging-related comorbid diseases such as Alzheimer's disease, cerebrovascular dementia, and sarcopenia. Here, correlative and causal links between diseases of overnutrition and diseases of aging and cognition are explored.
Keywords: Adipose Tissue; Aged; Aging; Animals; Bariatric Surgery; Brain; Cognition Disorders; Dementia; Diabetes Mellitus, Type 2; Disease Models, Animal; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Mice; Middle Aged; Muscle Weakness; Muscle, Skeletal; Nerve Net; Obesity; Overnutrition; Sarcopenia